1996
DOI: 10.1515/hfsg.1996.50.5.449
|View full text |Cite
|
Sign up to set email alerts
|

Surface Changes on Acetylation and Exposure to Ultraviolet Radiation of Pinus radiata Using X-Ray Photo-Electron Spectroscopy

Abstract: Various Pinus radiata wood components, solvent extracted and acetylated, were irradiated with ultraviolet light (λ, η ηχ = 350ηιτι). The XPS spectrum of the acetylated wood surface resembled that of cellulose acetate suggesting that acetylation removes lignin from the wood surface. The presence of acelylaled lignin in the acetic anhydride solution following acetylation, identified by IR and NMR, supports this theory. This could be a major contributor to the bleaching of wood on acetylation. The XPS spectra of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…However, acetylated wood only shows initial stability against UV radiation; later, it begins to fade and grey (Kalnins 1984, Hon 1995, Torr et al 1996, Ota et al 1996, 1997, Ohkoshi 2002, Mitsui -Tolvaj 2004, 2005. This is also true for Accoya® Radiata pine (Meyer 2006, Lahtela -Kärki 2015.…”
Section: Introductionmentioning
confidence: 97%
“…However, acetylated wood only shows initial stability against UV radiation; later, it begins to fade and grey (Kalnins 1984, Hon 1995, Torr et al 1996, Ota et al 1996, 1997, Ohkoshi 2002, Mitsui -Tolvaj 2004, 2005. This is also true for Accoya® Radiata pine (Meyer 2006, Lahtela -Kärki 2015.…”
Section: Introductionmentioning
confidence: 97%
“…Depolymerisation of cellulose and erosion of the middle lamella still takes place after acetylation, but mass loss is reduced and latewood cells maintain their structure [ 155 ]. It has been established that acetylation is ineffective in protecting lignin at wood surfaces during accelerated weathering [ 149 , 155 , 168 , 169 ], although some photoprotective effects of acetylation to 20% weight gain have been reported on holocellulose and on the morphology of wood cell walls [ 155 , 170 , 171 ]. However, acetylation is also reported to inhibit discolouration during UV exposure through a reduction of the formation of coloured chromophores on the wood surface [ 152 , 153 ].…”
Section: Chemical Modification Of Woodmentioning
confidence: 99%
“…They found that the O/C atom ratio increases and significant changes are apparent in the Cls spectra but not in the Ols spectra. The XPS spectra of irradiated wood and lignin showed that photo-oxidation had occurred in both extracted wood, untreated lignin, and acetylated samples [107]. UV weathering performance of polyvinyl chloride (PVC) containing different concentrations of wood powder was studied by Matuana and Kamdem (2002) based on the assessment of XPS data and other test results.…”
Section: Chemical Changes During Weatheringmentioning
confidence: 99%